2020
DOI: 10.3390/cells9122719
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A1 Released in Extracellular Vesicles by Pancreatic Cancer Cells Activates Components of the Tumor Microenvironment, through Interaction with the Formyl-Peptide Receptors

Abstract: Pancreatic cancer (PC) is one of the most aggressive cancers in the world. Several extracellular factors are involved in its development and metastasis to distant organs. In PC, the protein Annexin A1 (ANXA1) appears to be overexpressed and may be identified as an oncogenic factor, also because it is a component in tumor-deriving extracellular vesicles (EVs). Indeed, these microvesicles are known to nourish the tumor microenvironment. Once we evaluated the autocrine role of ANXA1-containing EVs on PC MIA PaCa-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 74 publications
(85 reference statements)
3
41
0
Order By: Relevance
“…In addition, in this case, we used as control the endothelial cells in the presence of their own growth medium (ctrl) and with HUVEC medium: macrophage growth medium 1:1 (ctrl sup). The experimental point with Ac2-26 was not explained because it was already shown in our previous study [34]. These results highlighted by the fluorescence images have been also proved by the histograms representing the densitometry analysis performed has reported in the Material and Methods section (Figure 4G).…”
Section: The Influence Of Wt Mia Paca-2 Evs On Endothelial Cell Activationsupporting
confidence: 69%
See 2 more Smart Citations
“…In addition, in this case, we used as control the endothelial cells in the presence of their own growth medium (ctrl) and with HUVEC medium: macrophage growth medium 1:1 (ctrl sup). The experimental point with Ac2-26 was not explained because it was already shown in our previous study [34]. These results highlighted by the fluorescence images have been also proved by the histograms representing the densitometry analysis performed has reported in the Material and Methods section (Figure 4G).…”
Section: The Influence Of Wt Mia Paca-2 Evs On Endothelial Cell Activationsupporting
confidence: 69%
“…MIA PaCa-2 cells (ATCC ® CRL-1420; Manassas, VA, USA) were grown as reported in [34]. ANXA1 knockout (KO) MIA PaCa-2 cells were generated as described in [15] and kept in selection by 700 µg/mL neomycin (Euroclone; Milan, Italy).…”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…In addition to its relationship with cancer cells, ANXA1 expression is also associated with multiple cells in the TME, such as fibroblasts, and, with angiogenesis, the generation of new vessels and metastasis [16,17]. Novizio et al reported that the ANXA1 extracellular vesicle (EV) complex participates in tumor cells-stroma intercommunication as a vehicle during PC progression, suggesting that ANXA1 may have potential prognostic and diagnostic roles [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, tumor cells were required to already be present at the future metastatic site in order for EVs to be able to enhance PSC migration and recruitment, as EVs are not a source of PDGFb [ 66 ]. Besides miRNAs and TGFb, Novizio et al reported that Annexin A1 released in PCC-EVs drives a mesenchymal switch and turns fibroblasts into myofibroblasts through Formyl Peptide Receptors (FPRs) activation [ 67 ]. Tumor cell-derived EVs isolated from PDA patient sera, as with other carcinoma cell lines, mediate the transfer of mRNA, such as that of telomerase—hTERT mRNA—to non-telomerase expressing somatic cells, fibroblasts, marking them with augmented proliferation and delayed senescence, as well as protection from DNA damage and subsequent apoptosis.…”
Section: Stromal Cells Evs-mediated Crosstalkmentioning
confidence: 99%